2020
DOI: 10.1259/dmfr.20190157
|View full text |Cite
|
Sign up to set email alerts
|

IAEA survey of dental cone beam computed tomography practice and related patient exposure in nine Central and Eastern European countries

Abstract: Objectives: Cone beam CT (CBCT) in dentistry and maxillofacial surgery is a widely used imaging method for the assessment of various maxillofacial and dental pathological conditions. The objective of this study was to summarize the results of a multinational retrospective–prospective study that focused on patient exposure in this modality. Methods: The study included 27 CBCT units and 325 adult and paediatric patients, in total. Data on patients, clinical indications, technical parameters of exposure, patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Widely varying non-optimised doses were also found for example in the SEDENTEXCT research project [40] and in the European DIMITRA (dentomaxillofacial paediatric imaging: an investigation toward lowdose radiation induced risks) project [50]. A recent study by the IAEA [51] revealed that optimisation in dental and maxillofacial CBCT imaging was still not at a mature stage, 7 years after the publication of SEDENTEXCT guidelines. This conclusion was also supported by a survey performed by the EURADOS working group 12 [47].…”
Section: Patient Dose and Optimisation Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Widely varying non-optimised doses were also found for example in the SEDENTEXCT research project [40] and in the European DIMITRA (dentomaxillofacial paediatric imaging: an investigation toward lowdose radiation induced risks) project [50]. A recent study by the IAEA [51] revealed that optimisation in dental and maxillofacial CBCT imaging was still not at a mature stage, 7 years after the publication of SEDENTEXCT guidelines. This conclusion was also supported by a survey performed by the EURADOS working group 12 [47].…”
Section: Patient Dose and Optimisation Aspectsmentioning
confidence: 99%
“…CBCT dosimetry still lacks a consensus on dose metrics at a practical level (KAP vs. CTDI, or some other dose quantity) [47,51]. This may also have implications on optimisation, as comparisons of dose levels between clinics, or even between different vendors or models, may be difficult.…”
Section: Dosimetry and Use Of Diagnostic Reference Levelsmentioning
confidence: 99%
“…An additional consideration is the wide range in image quality and radiation dose between CBCT machines, or between different exposure protocols of a CBCT unit. The imaging performance of CBCT is dictated by several factors, including but not limited to kV, mAs, and voxel size, which are not standardized between manufacturers or clinics 15,16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…While the diagnostic bene t of CBCT over 2D radiography is demonstrable, one should also consider the radiation risk 15 . An additional consideration is the wide range in image quality and radiation dose between CBCT machines, or between different exposure protocols of a CBCT unit.…”
Section: Discussionmentioning
confidence: 99%
“…CBCT guidelines in the North America conclude that the selected field-of-view (FOV) is an important consideration to reduce to dose to the patient [ 16 ]. The size and positioning of FOV affect the effective radiation dose [ 8 , 10 , 11 , 17 ]. Using small FOV (< 10 cm height), compared to large FOV sizes (> 15 cm height), the mean effective doses could decrease by 60% [ 18 ].…”
Section: Introductionmentioning
confidence: 99%